Universal design for learning in the early childhood classroom teaching children of all languages, cultures and abilities, birth-8 years - Brillante, Pamela; Nemeth, Karen (Routledge, 2018)
"Universal Design for Learning in the Early Childhood Classroom focuses on proactively designing PreK through Grade 3 classroom environments, instruction, and assessments that are flexible enough to ensure that teachers can accommodate the needs of all the students in their classrooms. Typically developing students, gifted students, students who are impacted by poverty, children who speak multiple languages or have a home language that is different than the classroom language, and students with identified or potential developmental or learning disabilities are all covered within this highly practical, easy-to-use guide to UDL in the early years."--Provided by publisher.